Inhibition of TLR4/MAPKs Pathway Contributes to the Protection of Salvianolic Acid A Against Lipotoxicity-Induced Myocardial Damage in Cardiomyocytes and Obese Mice - Yang, Zhen; Chen, Yanli; Yan, Zhaoyuan; Xu, Tian Tian; Wu, Xiangyao; Pi, Aiwen; Liu, Qingsheng; Chai, Hui; Li, Songtao; Dou, Xiaobing (Frontiers in Pharmacology, 2021)
Lipotoxicity is detrimental during obesity-associated cardiomyopathy. Salvianolic acid A (SAA), a natural polyphenol extracted from Radix Salvia miltiorrhiza (Danshen in China), is known to be cardioprotective. However, its benefits against obesity-associated cardiomyocyte injury are unclear. Here, we evaluated SAA’s protectiveness against lipotoxicity-induced myocardial injury and underlying mechanisms, in high fat diet (HFD)-fed mice and in palmitate-treated cardiomyocyte cells (H9c2). Our analysis of aspartate aminotransferase and creatine kinase isoenzyme-MB (CM-KB) levels show that SAA significantly reversed HFD-induced myocardium morphological changes and improved myocardial damage. SAA pretreatment ameliorated palmitic acid-induced myocardial cell death and was accompanied by mitochondrial membrane potential and intracellular reactive oxygen species improvement. Analysis of the underlying mechanisms showed that SAA rescued myocardial TLR4 induction in HFD-fed mice and H9c2 cells. Palmitic acid-induced cell death was significantly reversed by CLI-95, a specific TLR4 inhibitor. TLR4 activation with LPS markedly suppressed SAA-mediated protection from lipotoxicity. Additionally, SAA reduced lipotoxicity-driven expression of TLR4 target genes, including MyD88 and p-JNK/MAPK in HFD-fed mice and H9c2 cells. SAA did not affect palmitic acid-induced SIRT1 suppression and p-AMPK induction. Collectively, our data show that SAA protects lipotoxicity-triggered myocardial damage via a TLR4/JNK MAPK mediated mechanism.